Balancing chemical equations - Launchpad Multimedia (United Kingdom: Launchpad Multimedia)
Allows students to explore the Periodic Table and the balancing of chemical equations
System requirements: Pentium II or poer Mac, Windows 95 or later Mac OS 7 or later, 64 MB RAM, 8x cd-rom drive, 16 bit cound card with speakers, color monitor supporting 640 x 480 resolution and displaying 16 bit colour
Keywords: Chemical equations -- Software; Chemistry -- Software